Changing the Rules of the Game: How Do We Measure Success in Social Media? - Hogan, Aisling M.; Winter, Desmond C. (Clinics in Colon and Rectal Surgery, 2017)
Ours will be the generation proud to say we shifted the sands of educational deserts by open access and proliferation, seeding of data sharing, and watering grassroots research in resource-compromised environments. Universal “social” media is defining features of modern professional life that provide powerful modes of knowledge acquisition/sharing to that end. Altmetric and other measurements stratify academic communications according to this alternate, online media presence (not academic penetrance). Are they meaningless, self-absorbed integers, or reliable yardsticks of scientific and educational prowess? Far beyond this trite, patronizing question from the minds of outdated, terrified technophobes, the real impact of “social” media is not narcissistic solipsism. Instant dissemination of contemporary surgical controversies on a truly global level drives improved (or at least reflective) health care for all. While a numerical assignment of value according to views, “likes,” impressions, or “retweets” may seem meaningless to cynical, established academics, the impetus for universal improvement is self-evident. Electronic data and opinion sharing may not balance the inequity between low- and high-income countries, but it keeps it in perspective. The best way to shift desert sands is to blow on them constantly.
Keywords: social media; Twitter; altmetrics; Publons